2020
DOI: 10.1007/s40037-020-00562-8
|View full text |Cite
|
Sign up to set email alerts
|

Impostorism in third-year medical students: an item analysis using the Clance impostor phenomenon scale

Abstract: Introduction Impostorism, feelings of distrust in one's abilities and accomplishments despite evidence to the contrary, is frequent in medical students and negatively affects student wellness. Methods The aspects of impostorism that were most prevalent in medical students during the transition from the preclinical to clinical phases of their training were assessed using an anonymous, voluntary 60item survey that included the Clance Impostor Phenomenon Scale (CIPS) and a 2-item burnout assessment administered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 50 publications
1
51
0
2
Order By: Relevance
“…Third-year medical students identified most strongly with items related to unfounded fear of failure, hesitance to share recognition before it is announced, remembering failures rather than successes, believing themselves less capable than others, and worrying about succeeding. 7 I can honestly say that I have struggled with this on and off throughout my life. It all started from the very beginning of my medical career when I joined pre-medical entrance preparation session.…”
Section: My Own Strugglementioning
confidence: 96%
See 1 more Smart Citation
“…Third-year medical students identified most strongly with items related to unfounded fear of failure, hesitance to share recognition before it is announced, remembering failures rather than successes, believing themselves less capable than others, and worrying about succeeding. 7 I can honestly say that I have struggled with this on and off throughout my life. It all started from the very beginning of my medical career when I joined pre-medical entrance preparation session.…”
Section: My Own Strugglementioning
confidence: 96%
“… 6 Third-year medical students identified most strongly with items related to unfounded fear of failure, hesitance to share recognition before it is announced, remembering failures rather than successes, believing themselves less capable than others, and worrying about succeeding. 7 …”
Section: My Own Strugglementioning
confidence: 99%
“…4,6 Majority of medical students on the clinical phase of their training indicate moderate-to-strong impostor feelings. 7 Literature on imposter syndrome regarding education during the pandemic is limited. Burnout and imposter phenomenon can significantly impact medical education.…”
Section: Correspondence Tomentioning
confidence: 99%
“…A new study has shown that most medical students experienced moderate-to-strong IP 22 . The preclinical move to the clinical phases can be particularly challenging and exhibit low con dence during this time among medical students 23,24 .…”
Section: Introductionmentioning
confidence: 99%